Data linkage between the national birth defects prevention study and the occupational information network (O*NET) to assess workplace physical activity, sedentary behaviors, and emotional stressors during pregnancy. Issue 2 (17th December 2015) - Lee, Laura J.; Symanski, Elaine; Lupo, Philip J.; Tinker, Sarah C.; Razzaghi, Hilda; Pompeii, Lisa A.; Hoyt, Adrienne T.; Canfield, Mark A.; Chan, Wenyaw; ,
Abstract : Background: Knowledge of the prevalence of work‐related physical activities, sedentary behaviors, and emotional stressors among pregnant women is limited, and the extent to which these exposures vary by maternal characteristics remains unclear. Methods: Data on mothers of 6, 817 infants without major birth defects, with estimated delivery during 1997 through 2009 who worked during pregnancy were obtained from the National Birth Defects Prevention Study. Information on multiple domains of occupational exposures was gathered by linking mother's primary job to the Occupational Information Network Version 9.0. Results: The most frequent estimated physical activity associated with jobs during pregnancy was standing. Of 6, 337 mothers, 31.0% reported jobs associated with standing for ≥75% of their time. There was significant variability in estimated occupational exposures by maternal age, race/ethnicity, and educational level. Conclusions: Our findings augment existing literature on occupational physical activities, sedentary behaviors, emotional stressors, and occupational health disparities during pregnancy. Am. J. Ind. Med. 59:137–149, 2016. © 2015 Wiley Periodicals, Inc.